Chronic Ethanol Consumption Impairs the Tactile-Evoked Long-Term Depression at Cerebellar Molecular Layer Interneuron-Purkinje Cell Synapses in vivo in Mice - Li, Da-Yong; Bing, Yan-Hua; Chu, Chun-Ping; Cui, Xun; Cui, Song-Biao; Qiu, De-Lai; Su, Li-Da (Frontiers in Cellular Neuroscience, 2019)
Cerebellum is sensitive to ethanol (EtOH) consumption. Chronic EtOH consumption impairs motor learning by modulating cerebellar circuitry synaptic transmission and long-term plasticity. Under in vitro conditions, acute EtOH inhibits both parallel fiber and climbing fiber long-term depression (LTD). However, it has not been investigated thus far how chronic EtOH consumption affects sensory stimulation-evoked LTD at molecular layer interneurons (MLI) to PC synapses (MLI-PC LTD) in the cerebellar cortex of living animals. We here investigated the effect of chronic EtOH consumption on facial stimulation-evoked MLI-PC LTD, by electrophysiological technique and pharmacological methods in urethane-anesthetized mice. Our results showed that facial stimulation induced MLI–PC LTD in control mice, but it could not be induced in chronic EtOH consumption mice (0.8 g/kg; 28 days). Blocking cannabinoid type 1 (CB1) receptors activity with AM-251 prevented MLI-PC LTD in control mice, but revealed a nitric oxide (NO)-dependent long-term potentiation of MLI–PC synaptic transmission (MLI-PC LTP) in EtOH consumption mice. Notably, application of NO donor, SNAP alone prevented the induction of MLI–PC LTD, but a mixture of SNAP and AM-251 revealed a MLI-PC LTP in control mice. In contrast, inhibiting NOS revealed the facial stimulation-induced MLI-PC LTD in EtOH consumption mice. These results indicate that long-term EtOH consumption can impair the sensory stimulation-induced MLI–PC LTD via activation of NO signaling pathway in cerebellar cortex in vivo in mice. Our results suggest that the chronic EtOH exposure deficits cerebellar motor learning function may be involved in the impaired MLI–PC GABAergic synaptic plasticity.